Ecological Restoration of Antibiotic-Disturbed Gastrointestinal Microbiota in Foregut and Hindgut of Cows - Ji, Shoukun; Jiang, Tao; Yan, Hui; Guo, Chunyan; Liu, Jingjing; Su, Huawei; Alugongo, Gibson M.; Shi, Haitao; Wang, Yajing; Cao, Zhijun; Li, Shengli (Frontiers in Cellular and Infection Microbiology, 2018)
Antibiotically disturbed gastrointestinal microbiota needs a long period time to be restored to normal, which may cause a series of problems to the host. The understanding of restoration of the biased microbiota by antibiotics remains largely unknown. Here, we investigated the microbiota shift in foregut (rumen) and hindgut (rectum) of lactating cows after antibiotics exposure as well as after antibiotics withdrawal with (Microbiota transplantation, MT group) or without (Control, CON group) microbiota transplantation. We were able to demonstrate that microbiota in both foregut and hindgut significantly changed after 3 or 14 days of antibiotics exposure, and the changes persisted over long period of time (>18 days) after withdrawing the antibiotics. We further observed a faster restoration of microbiota in both foregut and hindgut of MT group than CON group, microbiota in foregut was mainly benefited from microbiota transplantation by restoring the alpha-diversity as well as within-group similarity, while microbiota in hindgut was primarily benefited from microbiota transplantation by reestablishing the co-occurrence network (nodes number, edges number, density, modularity as well as closeness centrality). These results together expanded our understanding of restoration of the biased microbiota by antibiotics, and may also be instructive to deal with the delayed microbiota restoration at least in cows.